Tantalum pentoxide ceramic coatings deposition on Ti4AI6V substrates for biomedical applications - Donkov, N.; Zykova, A.; Safonov, V.; Rogowska, R.; Smolik, J.; Luk’yanchenko, V. (Вопросы атомной науки и техники, 2011)
Tantalum pentoxide ceramic coatings are presented as perspective biomaterials for various biomedical applications. The surface properties and structure of as-deposited, annealed at 450°C and 700°C e-beam evaporated Ta2O5 films on Ti alloy substrates (Ti4Al6V) were investigated. The results demonstrated the good cyto compatibility of e-beam evaporated Ta2O5 coatings especially in the case of annealed films with strong stoichiometric Ta2O5 composition. Replacing the surface bounds with oxygen by either thermal or plasma treatment results in shear at more chemically stable hydrophilic surface region. Запропоновано керамічні покриття пентоксида танталу як перспективні біоматеріали для різноманітного біомедичного застосування. Було досліджено структуру та поверхневі властивості плівок Ta2O5, нанесених на зразки сплаву титана Ti4Al6V електронно-променевим випарюванням та відпалених при температурах 450 та 700°C. Результати довели гарну цитосумісність покриттів Ta2O5, особливо у випадку покриттів стехіометричного складу після термічної обробки. Заміщення поверхневих сполук киснем у процесі термічної або плазмової обробки зсуває поверхневі властивості у більш хімічно-стабільну гідрофільну зону. Керамические покрытия пентоксида тантала рассматриваются как перспективный биоматериал для различных биомедицинских целей. Исследованы структура и поверхностные свойства покрытий Ta2O5, нанесенных на подложки сплава титана Ti4Al6V электронно-лучевым испарением, и отожженных при температурах 450 и 700°C. Результаты показали хорошую цитосовместимость покрытий Ta2O5, особенно в случае отожженных покрытий стехиометрического состава. Замещение поверхностных связей кислородом в процессе термической или плазменной обработки сдвигает поверхностные свойства в более химически- стабильную гидрофильную область.